Analytical investigation of the control sysytem with delays - Sidekerskienė, Tatjana; Rimas, Jonas (Lietuvos matematikos rinkinys, 2021)
The forced synchronization system compared of n oscillators (n = 4, 6, 8) is analysed. Exact analytical expressions for elements of the step responsesmatrix of the system are derived.
Keywords: synchronization system; differential equation; delay